Early Modern Drama and the Bible
XI, 267 p.
Keywords: Early modern drama is steeped in biblical language, imagery and stories. This collection examines the pervasive presence of scripture on the early modern stage. Exploring plays by writers such as Shakespeare, Marlowe, Middleton, and Webster, the contributors show how theatre offers a site of public and communal engagement with the Bible.